2022
DOI: 10.1002/slct.202103559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and In Silico Studies of Some 2‐Substituted Benzoxazole Derivatives as Potential Anticancer Agents to Breast Cancer

Abstract: In an attempt to develop potent and selective anticancer agents, some 5‐ or 6‐ and N‐substituted benzoxazol‐2‐carboxamide derivatives were designed, synthesized, and evaluated for their cyclooxygenase inhibitory, antioxidant, and anti‐proliferative activity against MCF‐7 and MDA‐MB‐231 cell lines. Among them 5‐OMe, N‐piperidine substituted (compound 30), 5‐OMe, N‐4‐methylpiperidine substituted (compound 31) and 5‐Cl, N‐piperidine substituted (compound 34) benzoxazole 2‐carboxamide compounds have a moderate inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Antiproliferative activity results indicated that substituted benzimidazole derivatives positively affect the activity. Result analysis may conclude that compounds with aliphatic linkers (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) have good to potent antiproliferative activity with high selectivity. Interestingly, the antiproliferative activity study concluded that the 2-(aryl)benzimidazole derivatives would signi cantly lead to further investigation of antiproliferative activity by changing the substituted positions and designing new linkers with different heteroatoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antiproliferative activity results indicated that substituted benzimidazole derivatives positively affect the activity. Result analysis may conclude that compounds with aliphatic linkers (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) have good to potent antiproliferative activity with high selectivity. Interestingly, the antiproliferative activity study concluded that the 2-(aryl)benzimidazole derivatives would signi cantly lead to further investigation of antiproliferative activity by changing the substituted positions and designing new linkers with different heteroatoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the second group, 2-phenethylbenzimidazole derivatives (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), as presented in Table 2, were screened. Compound 44 was observed as the most potent antiproliferative agent against A-549 with an IC 50 value of 0.08 µM and possessed high selectivity against HEK293 with an IC 50 value of 1.00 µM, which means that it shows sixteen times more selectivity toward A549 cancer cell lines.…”
Section: Antiproliferative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods for preparation of benzothiazole‐ or benzoxazole‐2‐carboxamides reported in literature, [6b,10] some representative examples are shown on Scheme 1. The most frequently used way to benzothiazole‐2‐carboxamides employ condensation of 2‐aminobenzenethiol with diethyl oxalate or ethyl glyoxylate, hydrolysis of ester group and amidation (or direct amidation of ethyl benzothiazole‐2‐carboxylate with amines under microwave‐assisted or thermal conditions), [6a,c,11,16] similar method can be used for synthesis of benzoxazole‐2‐carboxamides from 2‐aminophenol [9] . Reaction of 2‐bromo‐2,2‐difluoroacetic acid amides with 2‐amino(thio)phenols in presence of S 8 was utilized to obtain heterocyclic amides [17] .…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used way to benzothiazole-2carboxamides employ condensation of 2-aminobenzenethiol with diethyl oxalate or ethyl glyoxylate, hydrolysis of ester group and amidation (or direct amidation of ethyl benzothiazole-2-carboxylate with amines under microwave-assisted or thermal conditions), [6a,c,11,16] similar method can be used for synthesis of benzoxazole-2-carboxamides from 2aminophenol. [9] Reaction of 2-bromo-2,2-difluoroacetic acid amides with 2-amino(thio)phenols in presence of S 8 was utilized to obtain heterocyclic amides. [17] Another way to benzoxazole-2-carboxamides employ oxidative cyclization of 2-((2hydroxyphenyl)amino)acetamides.…”
Section: Introductionmentioning
confidence: 99%